2016
DOI: 10.1093/jisesa/iew008
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Plant Volatile Compounds Reveals a High Affinity ofHylamorpha elegans(Coleoptera: Scarabaeidae) Odorant-Binding Proteins for Sesquiterpenes From Its Native Host

Abstract: Hylamorpha elegans (Burmeister) is a native Chilean scarab beetle considered to be a relevant agricultural pest to pasture and cereal and small fruit crops. Because of their cryptic habits, control with conventional methods is difficult; therefore, alternative and environmentally friendly control strategies are highly desirable. The study of proteins that participate in the recognition of odorants, such as odorant-binding proteins (OBPs), offers interesting opportunities to identify new compounds with the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 67 publications
(93 reference statements)
1
9
0
Order By: Relevance
“…It is also worth noting that a previous study obtained similar results using docking energies for DEET (Δ G = −5.86 kcal mol –1 ; K i = 50.51 μM) and potential repellents of Agam OBP1, such as 2-methyl-1-(1-oxodecyl)piperidine (Δ G = −7.36 kcal mol –1 ; K i = 4.04 μM), 1-(1-oxoundecyl)piperidine (Δ G = −7.20 kcal mol –1 ; K i = 5.28 μM), and N , N -diethyl-3-phenylpropanamide (Δ G = −6.49 kcal mol –1 ; K i = 17.21 μM). 39 Similarly, a previous study performed binding free energy calculations using the MM/GBSA method for β-caryophyllene (sesquiterpene), β-myrcene (monoterpene), and cis -β-ocimene (monoterpene) complexed to different OBP classes of Hydroides elegans , and their energy values approximated our calculated values of OBP1, 13 which is also consistent with the inhibitory activity.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is also worth noting that a previous study obtained similar results using docking energies for DEET (Δ G = −5.86 kcal mol –1 ; K i = 50.51 μM) and potential repellents of Agam OBP1, such as 2-methyl-1-(1-oxodecyl)piperidine (Δ G = −7.36 kcal mol –1 ; K i = 4.04 μM), 1-(1-oxoundecyl)piperidine (Δ G = −7.20 kcal mol –1 ; K i = 5.28 μM), and N , N -diethyl-3-phenylpropanamide (Δ G = −6.49 kcal mol –1 ; K i = 17.21 μM). 39 Similarly, a previous study performed binding free energy calculations using the MM/GBSA method for β-caryophyllene (sesquiterpene), β-myrcene (monoterpene), and cis -β-ocimene (monoterpene) complexed to different OBP classes of Hydroides elegans , and their energy values approximated our calculated values of OBP1, 13 which is also consistent with the inhibitory activity.…”
Section: Resultssupporting
confidence: 84%
“…Several studies have reported the specific inhibitory activity of some NPs from essential oil against insect OBPs with satisfactory binding affinity, such as sesquiterpenes (e.g., benzaldehyde, β-myrcene, and α-copaene) 13 and alcohols (e.g., n -decanol and n -dodecanol). 12 In the present study, we identified that predominantly monoterpenoids, such as p -cymen-8-yl, thymol acetate, and carvacryl acetate, mimic the binding mode of DEET, exhibiting similar pharmacophoric groups and intermolecular interactions with the protein pocket, which sheds light on the molecular mechanism of action of these compounds against olfactory recognition of insects, reinforcing the previous experimental repellency studies for this chemical class.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these previous researches, it is possible to conclude that the OBPs we identify within our current study (i.e., those that are expressed in nonolfactory tissues) may have other physiological or chemosensory functions. Here we propose that these proteins may participate in other chemosensory functions, such as the modulation of gustation, as opposed to (or in conjunction with) any role in olfaction (Blomquist and Vogt, 2003;Leal, 2005;Ling et al, 2014;Gonzalez-Gonzalez et al, 2016;Zhu et al, 2016). The additional OBPs we identify that are abundantly or specifically expressed in the B. dorsalis head may also function in olfaction because the maxillary palps were not explicitly removed in our experiments.…”
Section: Discussionmentioning
confidence: 92%
“…Although the chemical communication of the species has been studied, and the ability of males to perceive receptive females was reported (Quiroz et al, 2007) , very little is known about the molecular basis of H. elegans olfaction and chemical communication. However, a recent report revealed an olfactory protein linked to the ability to perceive volatiles commonly used in chemical communication by Scarabaeidae species (Venthur et al, 2014; González-González et al, 2016), which suggests that a similar mechanism could be involved in chemical communication in H. elegans .…”
Section: Introductionmentioning
confidence: 99%